2017
DOI: 10.1016/j.soilbio.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil microbial functional genes to global changes are indirectly influenced by aboveground plant biomass variation

Abstract: a b s t r a c tGlobal nitrogen (N) deposition and precipitation change are two important factors influencing the diversity and function of terrestrial ecosystems. While considerable efforts have been devoted to investigate the responses of aboveground plant communities to altered precipitation regimes and N enrichment, the variations of belowground soil microbial communities are not well understood, particularly at the functional gene structure level. Based on a 9-year field experiment established in a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 74 publications
2
56
2
Order By: Relevance
“…After SND, F:B decreased due to the decline in C:N, mainly because K-strategy fungi had higher biomass C:N than bacteria [3]. Li et al [48] suggested that N deposition can increase the soil MBC content, thus increasing MBC:MBN and reducing competition between plants and microorganisms [58]. Our results showed some differences from those conclusions, as they indicated that MBC decreased while MBC:MBN changed little.…”
Section: Discussioncontrasting
confidence: 75%
“…After SND, F:B decreased due to the decline in C:N, mainly because K-strategy fungi had higher biomass C:N than bacteria [3]. Li et al [48] suggested that N deposition can increase the soil MBC content, thus increasing MBC:MBN and reducing competition between plants and microorganisms [58]. Our results showed some differences from those conclusions, as they indicated that MBC decreased while MBC:MBN changed little.…”
Section: Discussioncontrasting
confidence: 75%
“…Soil samples were passed through a 2.0 mm sieve and stored at 4 °C before soil property analysis, and −80 °C before soil genomic DNA extraction. Soil physicochemical properties, including total carbon (TC), total nitrogen (TN), C/N ratio, total phosphorous (TP), total sulfur (TS), nitrate-N (NO 3 − -N) and ammonium-N (NH 4 + -N), dissolved organic carbon (DOC), moisture, and pH were determined by regular methods as described previously (Li et al 2016;Li et al 2017). Soil microbial biomass carbon (MBC) and nitrogen (MBN) were determined using the fumigation-extraction method (Brookes et al 1985).…”
Section: Soil Collection and Analysismentioning
confidence: 99%
“…A study in a long-term grassland experimental site revealed that DOC is the key factor directly determining soil microbial diversity [52]. As a substrate of microbial metabolic processes, DOC is of great significance to microbial assimilation and dissimilation [52].…”
Section: Discussionmentioning
confidence: 99%